Next-generation ammonia pretreatment enhances cellulosic biofuel production - Sousa, Leonardo da Costa; Jin, Mingjie; Chundawat, Shishir P. S.; Bokade, Vijay V.; Tang, Xiaoyu; Azarpira, Ali; Lu, Fachuang; Avci, Utku; Humpula, James; Uppugundla, Nirmal; Gunawan, Christa; Pattathil, Sivakumar; et al. (Energy & Environmental Science, 2016)
A new liquid ammonia pretreatment methodology called Extractive Ammonia (EA) was developed to simultaneously convert native crystalline cellulose I-beta (CI) to a highly digestible cellulose IIII (CIII) allomorph and selectively extract up to B45% of the lignin from lignocellulosic biomass with near-quantitative retention of all polysaccharides. EA pretreated corn stover yielded a higher fermentable sugar yield compared to the older Ammonia Fiber Expansion (AFEX) process while using 60% lower enzyme loading. The EA process preserves extracted lignin functionalities, offering the potential to co-produce lignin-derived fuels and chemicals in the biorefinery. The single-stage EA fractionation process achieves high biofuel yields (18.2 kg ethanol per 100 kg untreated corn stover, dry weight basis), comparable to those achieved using ionic liquid pretreatments. The EA process achieves these ethanol yields at industrially-relevant conditions using low enzyme loading (7.5 mg protein per g glucan) and high solids loading (8% glucan, w/v).

Whole genome sequencing and comparative genomics of Indian isolates of wheat spot blotch pathogen bipolaris sorokiniana reveals expansion of pathogenicity gene clusters - Yadav, Sagar; Raazi, Zarrine; Shivaraj, Sheelavanta Matha; Somani, Deepika; Prashant, Ramya; Kulkarni, Abhijeet; Kumar, Rajeev; Biradar, Suma; Desai, Shreenivas; Kadoo, Narendra (Pathogens, 2023)
Spot blotch is a highly destructive disease in wheat caused by the fungal pathogen Bipolaris sorokiniana (teleomorph, Cochliobolus sativus). It is prevalent in warm and humid areas, including Africa, Asia, Latin America, and the USA. In the present study, twelve isolates of B. sorokiniana were collected from wheat fields in three different geographical locations in India. The pathogenicity of seven sporulating isolates was assessed on `DDK 1025', a spot blotch-susceptible wheat variety under greenhouse conditions. The isolate `D2' illustrated the highest virulence, followed by `SI' and `BS52'. These three isolates were sequenced using the Illumina HiSeq1000 platform. The estimated genome sizes of the isolates BS52, D2, and SI were 35.19 MB, 39.32 MB, and 32.76 MB, with GC contents of 48.48%, 50.43%, and 49.42%, respectively. The numbers of pathogenicity genes identified in BS52, D2, and SI isolates were 2015, 2476, and 2018, respectively. Notably, the isolate D2 exhibited a relatively larger genome with expanded arsenals of Biosynthetic Gene Clusters (BGCs), CAZymes, secretome, and pathogenicity genes, which could have contributed to its higher virulence among the tested isolates. This study provides the first comparative genome analysis of the Indian isolates of B. sorokiniana using whole genome sequencing.
Keywords: Bipolaris sorokiniana; CAZyme; comparative genomics; spot blotch; whole genome sequencing